Profil Komunikasi Antarbudaya Mahasiswa Bimbingan dan Konseling - Herlina, Uray (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2017)
Communication is an essential tool for humans in fulfil the necessities of life and to attain the purpose of it. Communication and culture are two things that can not be separated like two sides of a coin. Studying communication means learn the culture, and viceversa. The purpose if this research to describe the profile of intercultural communication to students. The instrument that used was the inventory Guttman scale. Respondents of this research are students of IKIP PGRI Pontianak from every level of I, III, and V semester, with the total number of respondents are 66 people. The results showed in generally that the profile of intercultural communication among students has been good, where the cognitive, affective and psychomotor of student in every level of semester and ethnic are not much different. Hopefully this research can bethe foundation ofthe development of communication skills counseling on student guidance and counseling. Proper communication will bring success in relationship counseling for counselors and clients who come from different cultures.